DISCUSS ISSUES RELATED TO COMPARATIVE LITERATURE (BASED ON THE EXAMPLE OF TURKISH AND UZBEK LITERATURE) - D. Rasulmukhamedova; Kuchkarova Makhina Khojimuratovna (Western European Studies, 2024)
This article examines the issue of comparative analysis and its interpretation through an examination of two works: "Mehribonlar" by Uzbek writer Alp Jamal and "Bir vijdon uyg'onur" by Turkish writer Ahmad Lutfi Kazanchi. The subject of comparative literature, which is currently a significant area of interest within literary theory, is examined in detail. The present study analyses the works of these two renowned authors in accordance with the principles of comparative literary studies. Both writers are regarded as among the most esteemed and beloved creators of their respective nations. In examining their respective oeuvres and biographies, Alp Jamal and Ahmad Lutfi Kazanchi are regarded as two of the most significant and influential authors of their respective nations, exhibiting notable similarities in their lifestyles and approaches to creativity. Despite working in two distinct countries, these writers exhibit numerous similarities in their attitudes towards society, beliefs, and matters of religion and faith. The practice of comparison represents a highly effective method of literary analysis, with roots that extend back to the earliest days of literary history. The scope of comparative literature is extensive. In the field of contemporary literary studies, the concept of comparative literature is regarded as a relatively novel phenomenon, with its distinctive features becoming the focus of investigation in a range of academic disciplines. For example, works in Uzbek and English, Uzbek and Russian, Uzbek and French, and Uzbek and German literature are being extensively studied from a comparative perspective and have become the subject of research. A significant cohort of scholars specialising in comparative literature has emerged within Uzbek literary studies. Consequently, the principal focus of comparative literary studies is on the mutual literary connections between different works.
Keywords: Mehribonlar; Bir vijdon uyg'onur; novel; protagonist